2016
DOI: 10.1136/annrheumdis-2016-209124.100
|View full text |Cite
|
Sign up to set email alerts
|

A5.02 Fluorescence optical imaging coupled with ultrasound radiography for detecting subtle hand inflammation in early rheumatoid arthritis

Abstract: ObjectivesFluorescence Optical Imaging (FOI) is an emerging modality that uses an intravenous fluorophore to display altered microcirculation (abnormal perfusion/capillary leakage) in synovial tissues in the hands. FOI can be analyzed visually (FOI-v) or by using automated Disease ACTivity (DACT). Using musculoskeletal ultrasound (MSUS) as a validated reference measure, we previously showed FOI to be highly sensitive and specific in detecting clinically manifest and silent synovitis in patients with various rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…About two thirds of all new RA cases are mainly characterized by the presence of ACPA and RF autoantibodies and have genetic environmental risk factors, cytokine profiles and histology differences, and more joint destruction when left untreated as compared with seronegative RA cases (20). Previous reports also showed that in the presence or absence of RA‐related autoantibodies (ACPA or RF), the utility of imaging, especially radiography, MSUS, and FOI accompanied by the automated DACT‐FOI analysis, reliably supports the rheumatologist's decision‐making (6,8,18,19). Based on this RA subpopulation (Supplementary Figures 3 and 4), we showed the usefulness of FOI in identifying joint inflammation using ultrasound as a reference, to be 81% sensitive and 90% specific, with positive and negative predictive values of 96% and 61%, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…About two thirds of all new RA cases are mainly characterized by the presence of ACPA and RF autoantibodies and have genetic environmental risk factors, cytokine profiles and histology differences, and more joint destruction when left untreated as compared with seronegative RA cases (20). Previous reports also showed that in the presence or absence of RA‐related autoantibodies (ACPA or RF), the utility of imaging, especially radiography, MSUS, and FOI accompanied by the automated DACT‐FOI analysis, reliably supports the rheumatologist's decision‐making (6,8,18,19). Based on this RA subpopulation (Supplementary Figures 3 and 4), we showed the usefulness of FOI in identifying joint inflammation using ultrasound as a reference, to be 81% sensitive and 90% specific, with positive and negative predictive values of 96% and 61%, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports also showed that in the presence or absence of RA‐related autoantibodies (ACPA or RF), the utility of imaging, especially radiography, MSUS, and FOI accompanied by the automated DACT‐FOI analysis, reliably supports the rheumatologist's decision‐making (6,8,18,19). Based on this RA subpopulation (Supplementary Figures 3 and 4), we showed the usefulness of FOI in identifying joint inflammation using ultrasound as a reference, to be 81% sensitive and 90% specific, with positive and negative predictive values of 96% and 61%, respectively (8). Notably, FOI was 68% sensitive in detecting silent synovitis defined as not inflamed on CE, but synovitis positive on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations